2020
DOI: 10.1038/s41597-020-00714-9
|View full text |Cite
|
Sign up to set email alerts
|

A real-time survey on the psychological impact of mild lockdown for COVID-19 in the Japanese population

Abstract: To deter the spread of the coronavirus disease 2019 (COVID-19), many countries have imposed a lockdown with restrictions. On 7 April 2020, the Japanese government declared a state of emergency over the COVID-19 outbreak. Japan was in “mild lockdown” which was not enforceable and non-punitive with the declaration. We conducted an online survey to investigate factors associated with psychological distress in the “mild lockdown” under a declared state of emergency for COVID-19. We collected data on 11,333 inhabit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 38 publications
(42 reference statements)
1
30
0
2
Order By: Relevance
“…First, HbA1c values significantly increased among women but not among men with diabetes mellitus. A recent study conducted in Japan reported that psychological distress associated with the COVID-19 pandemic was significantly larger among women than among men [29]. Women tend to be more affected by the social and economic consequences of a pandemic than do men [30].…”
Section: Discussionmentioning
confidence: 96%
“…First, HbA1c values significantly increased among women but not among men with diabetes mellitus. A recent study conducted in Japan reported that psychological distress associated with the COVID-19 pandemic was significantly larger among women than among men [29]. Women tend to be more affected by the social and economic consequences of a pandemic than do men [30].…”
Section: Discussionmentioning
confidence: 96%
“…Based on previous literature regarding the COVID-19 pandemic [ 3 , 6 , 8 , 11 ], we developed eight lifestyle and stress management items (e.g., exercise, ‘I exercised for my health (whether indoors or outdoors)’) and seven stressors (e.g., deterioration of household economy, ‘The family budget has tightened’) that were assumed to be associated with mild lockdown ( Table 2 ). All details of the items are more extensively described on the Open Science Framework platform [ 38 ] and by Sugaya et al [ 39 ]. We asked participants to rate the frequency of implementation and experience of these items from the start of the mild lockdown to the time of the survey on a scale of 1 (not at all) to 7 (extremely).…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, there is a wide consensus that the COVID-19 pandemic has led to worldwide measures with severe consequences for millions of people (1)(2)(3). Several studies show, in fact, how this event generated a degree of malaise and psychological distress in the general population (4)(5)(6)(7)(8)(9)(10)(11)(12), in the adult clinical population (13,14) and in children and adolescents (15)(16)(17)(18)(19), showing a worsening of various clinical pictures and an increase in psychological difficulties.…”
Section: Introductionmentioning
confidence: 99%